Les Québécois d'origine italienne. Une longue histoire - Linteau, Paul-André (Cap-aux-Diamants, 2019)
Keywords: Italiens

Immigrants italiens dans l'espace social et culturel montréalais. Une synthèse historique - Ramirez, Bruno (Histoires d'immigrations à Montréal, 2014)
Keywords: Italiens

Histoire comparée de l’action politique au sein des communautés italiennes au Québec et en Suisse de 1945 à 1985 - Guerrera, Marco (Université de Montréal, 2003)
Keywords: Italiens

Fascisme et communauté italienne de Montréal d'après L'Italia Nuova - Laplante, Jacinthe (Université de Sherbrooke, 2008)
Keywords: Idéologies; Italiens

Réminiscences italiennes - Létourneau, Isabelle (Continuité, 2001)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Saint-Léonard, banlieue italienne: anatomie d'une mutation - Pazzi, Lara (Université du Québec et Institut national de la recherche scientifique, 2012)
Keywords: Italiens; Quartiers; Saint-Léonard

De la Toscane au Canada, les statuaires italiens - Tremblay, Marc Alain; Carli-Trudeau, Jocelyne F. (Cap-aux-Diamants, 2019)
Keywords: Arts sacrés; Italiens; Sculpture

Le comportement de consommation artistique et culturel des groupes ethniques à Montréal, le cas des Portugais, des Maghrébins et des Italiens - Paiement, Isabelle (Université du Québec à Montréal, 2000)
Keywords: Italiens; Maghrébins; Portugais

Entre rupture et transmission: les pratiques alimentaires italiennes autour du marché Jean-Talon - Masson-Labonté, Amélie; Gagnon, Marie-Anne (Cap-aux-Diamants, 2019)
Keywords: Alimentation; Italiens; Jardins; Marchés

La communauté italienne de Montréal en 1901 - Tonietto, Manon (Université du Québec à Montréal, 2004)
Keywords: Italiens; Quartiers; Saint-Jacques; Saint-Laurent (quartier)

Memoria e riconoscimento nella narrazione filmica degli italiani di Montréal - Ramirez, Bruno (À l'italienne. Narrazioni dell'italianità dagli anni Ottanta a oggi, 2018)
Keywords: Cinéma; Italiens

La letteratura dell'emigrazione italo-canadese di Montréal - Tedeschi, Antonio (Université McGill, 2000)
Keywords: Italiens

Guido Nincheri: le savoir-faire de la Renaissance italienne à Montréal - Busseau, Laurent (Histoire Québec, 2017)
Keywords: Arts sacrés; Peinture; Vitraux; Églises

Le triomphe de l’opéra italien à Montréal, de l’union des Canadas à la Grande Guerre - Barrière, Mireille (Cap-aux-Diamants, 2016)
Keywords: Opéra; Théâtre Royal

The Influence of Culture on Pro-Environmental Activities: Comparing English, French and Italian Canadians - Qian, Zhonglian Cindy (Université Concordia, 2001)
Keywords: Italiens

Italian Identity in Montreal: Issues of Intergenerational Ethnic Retention - De Martinis, Lucio (Université McGill, 2005)
Keywords: Italiens

Une communauté singulière. Les Pesaresi de Montréal - Perin, Roberto (Cap-aux-Diamants, 2019)
Keywords: Italiens

Dal Mediterraneo all’Atlantico: ricordi di migrazione nella Montréal del secondo dopoguerra - Piraro, Sergio (Italian Canadiana, 2021)
Keywords: Italiens

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Actor or Victim? Mario Duliani and His Internment Narrative - Perin, Roberto (Enemies Within: Italians and Other Internees in Canada and Abroad, 2000)
Keywords: Guerre; Italiens

The Internment of Italian Canadians - Bruti Liberati, Luigi (Enemies Within: Italians and Other Internees in Canada and Abroad, 2000)
Keywords: Italiens; Prisons

Italian Immigrant Women and Literacy: A Case Study - Constantino, Patricia (Université Concordia, 2001)
Keywords: Femmes; Italiens

''Tutti a Tavola!'' Feeding the Family in Two Generations of Italian Immigrant Households in Montreal - Cancian, Sonia (Edible Histories, Cultural Politics: Toward a Canadian Food History, 2012)
Keywords: Alimentation; Italiens

From Acculturation to Integration. The Political Participation of Montréal's ltalian-Canadian Community in an Urban Context (1945-1990) - Ricci, Amanda (Université de Montréal, 2009)
Keywords: Féminisme; Italiens

Migration, Settlement, and Television: The Montreal’s Teledomenica Experience - Ramirez, Bruno (Voices in Italian Americana, 2010)
Keywords: Italiens; Télévision

Les Italo-Montréalais [sic] et leur histoire (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2019)
Keywords: Italiens; Travail

Families, Lovers and their Letters: Italian Postwar Migration to Canada - Cancian, Sonia (Studies in Immigration and Culture, 2010)
Keywords: Famille; Femmes; Italiens

Les Italo-Montréalais [sic] et leur histoire (suite et fin) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2019)
Keywords: Guerre; Idéologies; Italiens

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

Leonardo da Montreal: The Rhetoric of Italianità and the Canadian Post-Nation - Fratiloiu, Raluca Maria (Université Concordia, 2006)
Keywords: Centre Leonardo Da Vinci; Italiens

Du Centro Donne Italiane di Montréal aux Donne d’Acciaio. - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2023)
Keywords: Ahuntsic; Femmes; Féminisme; Italiens

Une communauté en transition: la Petite Italie de Montréal - Del Balso, Michael (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Cultivating Heroes: From Dante and Caboto to Mussolini, the Public Art of Montreal's Italians in the 1920s-1930s - Carlevaris, Anna Maria (Université Concordia, 2004)
Keywords: Italiens; Monuments; Peinture; Sculpture

"My Love, How Different Life Is Here..." A Young Italian Woman's Impressions of Postwar Montreal - Cancian, Sonia (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Femmes; Italiens; Langue; Travail

Bienvenue dans la Petite-Italie de Montréal - Taschereau, Sylvie (Cap-aux-Diamants, 2019)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums

Women and Ethnic Language Maintenance: A Study of Italian Immigrant Family Triads in Saint-Léonard, Montréal - Venditti, Rosa L. (Université Concordia, 2003)
Keywords: Italiens; Langue; Quartiers; Saint-Léonard

Trajectoires et subjectivités italo-québécoises : le processus identitaire de la deuxième génération tel que conçu par Marco Micone, Mary Melfi et Paul Tana - Hélie-Martel, Anaïs (Université de Montréal, 2016)
Keywords: Cinéma; Italiens; Langue; Roman; Théâtre

Mille nuances pour un pays - Corriveau, Jeanne (Continuité, 2019)
Keywords: Chinois; Conservation; Italiens; Patrimoine; Syriens

Le " Michel-Ange de Montréal ": Guido Nincheri - Grondin, Mélanie (Cap-aux-Diamants, 2019)
Keywords: Arts sacrés; Italiens; Peinture; Vitraux; Églises

Le boulevard Saint-Laurent dans la Petite-Italie: 1930, 1960 - Trépanier, Mathieu Alexandre (Université du Québec à Montréal, 2014)
Keywords: Italiens; Petite-Italie (quartier); Quartiers; Rues; Saint-Laurent (rue)

There's No Place Like Home: Feminist Communities, Social Citizenship and (Un)Belonging in Montreal's Long Women's Movement, 1952-1992 - Ricci, Amanda (Université McGill, 2015)
Keywords: Anglophones; Autochtones; Femmes; Francophones; Féminisme; Haïtiens; Italiens; Noirs

Témoins discrets - Leclerc, Jean-François (Continuité, 2019)
Keywords: Chinois; Grecs; Irlandais; Italiens; Juifs; Noirs; Patrimoine; Syriens

La crise de Saint-Léonard dans la presse montréalaise, 1968-1969 - Chikli, Christophe (Université de Sherbrooke, 2006)
Keywords: Devoir (Le); Italiens; Langue; Montreal Gazette; Montreal Star; Presse (La); Saint-Léonard (crise de)

Les banlieues de l'immigration ou quand les immigrants refont les banlieues - Germain, Annick; Rose, Damaris; Richard, Myriam (Histoire de Montréal et de sa région, 2012)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

Building and Reshaping the Suburban Landscape: The Role of Immigrant Communities - Germain, Annick; Rose, Damaris; Richard, Myriam (Montreal: The History of A North American City, 2018)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard